The Effect of Inferior Oblique Muscle Z-Myotomy in Patients with Primary Inferior Oblique Overaction - Hasan Kızıltoprak; Hakan Halit Yaşar; Kemal Tekin (Türk Oftalmoloji Dergisi, 2020)

(untitled)
Objectives:To investigate the surgical results of the inferior oblique muscle Z-myotomy in patients with inferior oblique muscle overaction (IOOA).Materials and Methods:The medical records of patients who had undergone inferior oblique muscle Z-myotomy for primary IOOA in a single center between 2017 and 2018 were retrospectively analyzed. All patients had mild IOOA (+1 and between +1 and +2). Preoperative and postoperative IOOA degrees and ocular motility examinations were evaluated. Inferior oblique muscle Z-myotomy is performed at 6 mm along the physiological muscle line after identifying the lower oblique muscle through an inferotemporal fornix incision.Results:Forty-seven eyes of 44 patients were included in the study. The patients were divided into those with +1 IOOA (n=37, 78.7%) and those with +1-2 IOOA (n=10, 21.3%). The mean age of the +1 group was 14.18±11.8 years and the mean age of the +1-2 group was 13.40±7.45 years. The mean follow-up time was 10.56±8.7 (6-17) months. Bilateral Z-myotomy was performed in 3 (6.8%) and unilateral in 41 (93.2%) of the patients. IOOA correction was observed in 43 (91.4%) of the 47 eyes after Z-myotomy, while 4 (8.6%) eyes still had preoperative levels of IOOA. There was no statistically significant difference in surgical success rate between the groups (p=0.849). When preoperative and postoperative IOOA values were compared, there was a statistically significant decrease in IOOA values in the postoperative period (p=0.001). No intraoperative or postoperative complications were observed.Conclusion:Inferior oblique Z-myotomy is a simple, fast, sutureless surgical procedure in which the original muscle insertion is preserved. Z-myotomy of the inferior oblique muscle can be used as a successful attenuation method in patients with minimal IOOA.